2009
DOI: 10.3748/wjg.15.219
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of Helicobacter pylori extracts on gastric mucosal blood flow in the mouse

Abstract: A H pylori water extract reduces gastric mucosal blood flow acutely through iNOS- and nerve-mediated pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Judaki et al [18] reported more prominent vascular changes in patients with H. pylori-positive chronic gastritis than in H. pylori-negative chronic gastritis. Some studies have also reported decreased gastric microcirculation in patients with H. pylori infection [12,20]. These findings all show that both micro-and macrovascular changes occur in the presence of H.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Judaki et al [18] reported more prominent vascular changes in patients with H. pylori-positive chronic gastritis than in H. pylori-negative chronic gastritis. Some studies have also reported decreased gastric microcirculation in patients with H. pylori infection [12,20]. These findings all show that both micro-and macrovascular changes occur in the presence of H.…”
Section: Discussionmentioning
confidence: 55%
“…Platelet activating factor (PAF) released from mast cells and some other inflammatory cells is a potent vasoconstrictor. PAF causes early leukocyte migration and hypoperfusionin gastrointestinal microcirculatory [12]. Although few mast cells can be seen in normal mucosa, the level increases in the presence of inflammation [13].…”
Section: Discussionmentioning
confidence: 99%
“…An additional study confirmed these findings and identified significant albumin leakage, which suggested damage to the endothelium [27]. H. pylori infection in mice resulted in a 30% reduction in mucosal blood flow as evaluated by laser Doppler [46]. Clinically, H. pylori infection was associated with a decrease in mucosal blood flow in patients who had undergone endoscopic mucosal resection [47].…”
Section: Acute Infectionsmentioning
confidence: 71%
“…These systems are part of the pathogen protection against nitrosative stress . Likewise, Hp may exhibit a direct effect on the reduction in gastric mucosal blood flow by inhibiting NO production by iNOS, thereby decreasing the vasodilatory and mast cell–stabilizing action of NO . Moreover, several Hp virulence agents contribute to its ability to evade the immune system and disrupt host cells.…”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 99%